The Role of the REMAP Learning Model on Empowerment of Critical Thinking Skills Integrated with Sustainable Development Goals (SDGs) - Ferry Irawan; Hanip Rival; Riyana Minuk (Journal of Biology Learning, 2026)
The learning orientation is adjusted to the main objectives of the Sustainable Development Goals (SDGs) which direct students to solve problems scientifically through critical thinking. This study aims to determine the effectiveness of  the Remap STAD learning model  on the empowerment of students' critical thinking skills. This study is a type of experimental quasy research  and uses a non-equivalent pretest-posttest control group design. The population is all students of class XI SCIENCE SMAN 2 Barru totaling 234 students. A sample of 102 students was selected based on an equivalence test to determine experimental classes, positive controls, and negative controls. The instrument used the essay test was in accordance with the Critical Thinking skill indicator and the results were analyzed using the one-path anakova test. The results of the study show that the Remap  learning model is effective in empowering students' critical thinking skills